Preparation of a superior damping coating and study on vibration damping properties - Gen Jin; Guo Chen; Zihao Zhao; Zhengda Zhao; Lei Liu; Jin Qian (SN Applied Sciences, 2023)
Abstract In this paper, a superior damping coating was prepared, which can be easily sprayed onto the samples, showing a promising application in the vibration reduction for aircraft. This paper aims to investigate the effect of filler content, size and coating thickness on the damping properties of aluminum flake samples. It is found that the vibration of the sample is significantly suppressed with the vibration reduction rate of the coating reaching 63.23%. Moreover, the damping ratio of the coating was calculated using the half-power bandwidth method, based on which the finite element simulation model was established. The simulation results are in perfect agreement with the test ones, and the maximum vibration amplitude error stayed within 9.06%. These results fully demonstrated the effectiveness and practicality of the damping coating.